1996
DOI: 10.2337/diab.45.3.s114
|View full text |Cite
|
Sign up to set email alerts
|

Human Arterial Smooth Muscle Cell Proliferation in Diabetes

Abstract: In the present study, we focus on the proliferation of human arterial smooth muscle cells (SMCs) from NIDDM patients (DM-SMCs) to clarify the reactivity to the growth factor(s) in fetal calf serum (FCS) and the factor(s) secreted by T-cells. The proliferation of DM-SMCs was significantly greater than SMCs from nondiabetic patients (nonDM-SMC). DM-SMC conditioned medium (DM-condMed) increased the growth of nonDM-SMCs. These results suggest that the growth factor is secreted from DM-SMCs as an autocrine system, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 5 publications
3
20
1
Order By: Relevance
“…Studies in experimental animal models of diabetes and in humans demonstrated enhanced proliferation of aortic VSM cells (19,20). Also, porcine aortic VSM cells in culture exhibit increased cell proliferation under hyperglycemic conditions (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in experimental animal models of diabetes and in humans demonstrated enhanced proliferation of aortic VSM cells (19,20). Also, porcine aortic VSM cells in culture exhibit increased cell proliferation under hyperglycemic conditions (21).…”
Section: Discussionmentioning
confidence: 99%
“…Using this culture model, we reported that hypoxia induces proliferation, dedifferentiation, and/or extracellular matrix synthesis in cultured renal tubular epithelial and glomerular mesangial cells (16 -18). In the present study, we examined the effect of hypoxia on the proliferation of cultured rat aortic VSM cells to determine whether hypoxia directly alters their proliferative behavior.Enhanced proliferation of VSM cells has also been demonstrated in both human and experimental models of diabetes (19,20). In addition, cultured VSM cells grown in high media glucose concentration (to mimic hyperglycemia of diabetes) have exhibited increased cell proliferation (21).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Others have shown that hypoxia is also mitogenic to cultured pulmonary artery smooth muscle and endothelial cells (12,13,25). Prevalence of tissue hypoxia and increased VSM cell proliferation is also reported in experimental models of diabetes and hypertension (1,10,28,35,40,45). Elevated glucose concentrations in medium have been shown to produce both hypertrophic and hyperplastic effects in cultured porcine aortic smooth muscle cells (32).…”
mentioning
confidence: 99%
“…It has been reported that macrophages from diabetic patients showed accelerated cholesterol esterification when incubated in whole serum (8). We also have in vitro data that low density lipoprotein (LDL) obtained from diabetic patients strikingly simulated arterial smooth muscle cell-growth compared to LDL isolated from normal controls (9), and smooth muscle cells derived from diabetic patients proliferated more rapidly than those from normal subjects (10). In diabetes mellitus the function of arterial cells is altered by various factors.…”
Section: Introductionmentioning
confidence: 72%